Determination of phytochemical constituents, antibacterial and antioxidant activities of ethanolic leaf extracts of Pterocarpus erinaceus (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Okoli EC, Umaru IJ, Olawale O. 2023. Determination of phytochemical constituents, antibacterial and antioxidant activities of ethanolic leaf extracts of Pterocarpus erinaceus. Biodiversitas 24: 2272-2277. Many people in Nigeria and West Africa have long used the leaves, stem bark, and roots of Pterocarpus erinaceus Poir. as a medicine to treat ailments such as malaria, ulcers, coughs, and fevers. The antioxidant, antimalarial, antiulcer, and antibacterial activities of stem bark, leaves, and roots of P. erinaceus have been investigated. The aim of this study was to determine the phytochemical composition, antimicrobial activity, and antioxidant activity of the P. erinaceus leaf. Phytochemical compounds in ethanolic leaf extracts of P. erinaceus were analyzed and quantified by Gas Chromatography/Flame Ionization Detector (GC-FID). The antibacterial test was performed against Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeruginosa, and Escherichia coli by agar diffusion. The antioxidant activity was evaluated by DPPH scavenging activity. Phytochemicals content in the extract include flavonoids (44.71%), alkaloids (19.47%), steroids (6.01%), tannins (1.73%), saponins (4.70%), glycosides (7.00%), tannins (2.60%), anti-nutrient (12.77%). Ethanol extracts of P. erinaceus leaves were effective against all selected bacterial strains (E. coli, S. aureus, B. subtilis, and P. aeruginosa). DPPH scavenging activity of the ethanol extract of P.erinaceus at a concentration of 1000 ?g/mL was 49.51% and 27.20% at 40 ?g/mL, categorized as moderate antioxidant activity. This study showed that crude ethanol extracts of P. erinaceus leaf contained pharmacologically active compounds and exhibited significant antibacterial and DPPH free radical scavenging activities in a concentration-dependent manner.